Letter - Alvaro, Pablo
026-0088-001 Girton House Kingsway Hove - Sussex Secretary Assistance Trades Union Transport House Smith Square London, S.W.1 Hove 25th May 1939 Dear Sir We thank you for your letter of the 16th inst, in which you state you have sent us a parcel and we thank you for the very kind interest you take in us. We have not yet received the parcel and wonder of it may have been lost in the post. We mention this so that you could perhaps make enquiries about it. Thanking you once again Yours Very Sincerely Pablo Alvaro 292/946/26/88